Effect of manpower development on workers' job performance (2012)
This study examines the effect of manpower development on workers' job performance. The objectives of the study were to explain the concept of manpower development, determine if manpower development has effect on organizational performance, ascertain how to identify training and development needs in an organization, determine if lack of manpower development programmes leads to low productivity, and ascertain the link between poor development programmes and labour tunrover. The study outlines the benefits of manpower development in modern business organisation. One hundred employees of a manufacturing outfit were used as sample. Date from the study were analyzed using descriptive and inferential statistics particularly chi-square distribution test. Findings revealed that capital, equipment, manpower among others contributed to the company's success. The most significant of these was the human factor. This is so because it is the human who pools other resources together for objective realization. Thus, manpwer development should be given top priority management attention. Also, human beings constitute the ultimate basis of a nation's wealth and an organization's assets. Therefore, it is imperative for the organization to continuously build the capacity of its human capital on whom the huge responsibilities of achieving the organizational goals rest. It ws, therefore, recommended that organizations in Nigeria should embrace manpower development as corporate and management strategy to continuously improve knowledge, skills and attitude required by employees to perform creditably on a given task or job and cumulatively enhances organizational productivity and optimizes corporate profitability.